Nasal floor mucosal thickness in chronic rhinosinusitis: a computed tomography-based case-control study - Teixeira, Mónica; Cunha, André; Nazaré, Francisco; Schuknecht, Bernhard; Briner, Hans Rudolf (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Background: Tissue remodelling is a hallmark of chronic rhinosinusitis (CRS), yet the nasal floor has received little attention as a potential site of structural change. This study aimed to explore whether radiographic evidence of nasal floor mucosal thickening is a distinctive feature of CRS and a potential endotype marker. Methods: This case-control study included 80 patients with bilateral CRS who underwent endoscopic sinus surgery and 80 controls. Nasal floor mucosal thickness was measured at two points on coronal paranasal sinus computed tomography (CT): anteriorly, where the inferior turbinate inserts the maxilla, and posteriorly, at the nasolacrimal duct opening into the inferior meatus. Results: Mean nasal floor mucosal thickness was significantly greater in CRS patients than in controls at both anterior (2.52±0.74 mm vs. 2.02±0.59 mm) and posterior (2.05±0.63 mm vs. 1.52±0.44 mm) sites (p<0.001). Within the CRS cohort, anterior mucosal thickness was significantly higher in eosinophilic CRS compared to non-eosinophilic CRS patients (p=0.006). Conclusions: Increased nasal floor mucosal thickness is associated with CRS, particularly in the eosinophilic endotype. Given its simplicity and reproducibility, nasal floor thickness may support non-invasive endotype differentiation and aid in clinical decision-making. Further prospective studies are needed to validate its diagnostic and prognostic value.